Pegembangan Sumber Daya Manusia Bagi Tenaga Guru - H Hamsinah (Sosio-Didaktika: Social Science Education Journal, 2016)
Abstract: The research focused on the development of learning and training for teachers in the province of South Sulawesi, including the preparation of the strategy of training, teaching and training, and evaluation of training. The purpose of this study was to identify factors inhibiting and supporting human resource development for teachers in South Sulawesi. This type of research is qualitative descriptive study. The results showed that the development of human resources for teachers in South Sulawesi, especially in the process of learning and training, to achieve maximum results even though there are still many obstacles. Development and training learning model consists of the preparation strategy of training, teaching and training, as well as the evaluation phase of training, but its application is not at 100%, although at this stage of the training and learning process has been conducted in accordance with the planning and preparation strategy training predetermined.Abstrak: Penelitian ini difokuskan pada pengembangan pembelajaran dan pelatihan bagi guru di Provinsi Sulawesi Selatan, meliputi strategi persiapan pelatihan, proses pembelajaran dan pelatihan, serta evaluasi pelatihan. Tujuan penelitian ini adalah untuk mengidentifikasi faktor penghambat dan pendukung pengembangan sumber daya manusia bagi guru-guru di Sulawesi Selatan. Jenis penelitian adalah penelitian deskriptif kualitatif. Hasil penelitian menunjukkan bahwa pengembangan sumber daya manusia bagi guru-guru di Sulawesi Selatan, terutama dalam proses pembelajaran dan pelatihan, mencapai hasil yang maksimal meskipun masih terdapat berbagai kendala. Pengembangan dan pelatihan dengan model pembelajaran terdiri dari strategi persiapan pelatihan, proses pembelajaran dan pelatihan, serta tahap evaluasi pelatihan, namun penerapannya belum mencapai 100%, meskipun pada tahap pelatihan dan proses pembelajaran sudah dilaksanakan sesuai dengan perencanaan dan strategi persiapan pelatihan yang ditentukan sebelumnya.Pengutipan: Hamsinah. (2016). Pegembangan Sumber Daya Manusia Bagi Tenaga Guru.  SOSIO DIDAKTIKA: Social Science Education Journal, 3(1), 2016, 70-80. doi:10.15408/sd.v3i1.3799.Permalink/DOI: http://dx.doi.org/10.15408/sd.v3i1.3799